Head/neck pain characteristics after spontaneous cervical artery dissection in the acute phase and on a long-run. (August 2022) - Mayer-Suess, Lukas; Frank, Florian; Töll, Thomas; Boehme, Christian; Gizewski, Elke R; Ratzinger, Gudrun; Broessner, Gregor; Kiechl, Stefan; Knoflach, Michael
Objective: Head/neck pain is one of the primary symptoms associated with spontaneous cervical artery dissection. Still, data on pain quality, intensity, and long-term dynamics are scarce. Methods: Spontaneous cervical artery dissection subjects were included if mural hematoma was visualised through T1 fat-saturated MRI at baseline. All available medical records were evaluated and patients were invited to standardised clinical follow-up visits at least 1 year after the index event. Results: In total, 279 subjects were included in the ReSect-study with head/neck pain being the most frequent symptom of spontaneous cervical artery dissection (220 of 273, 80.6%). Pain was of pulling nature in 107 of 218 (49.1%), and extended to the neck area in 145 of 218 (66.5%). In those with prior headache history, pain was novel in quality in 75.4% (42 of 55). Median patient-reported pain intensity was 5 out of 10 with thunderclap-type headache being uncommon (12 of 218, 5.5%). Prior to hospital admission, head/neck pain rarely responded to self-medication (32 of 218, 14.7%). Characteristics did not differ between subjects with and without cerebral ischemia. Pain resolved completely in all subjects within a median of 13.5 days (IQR 12). Upon follow-up in 42 of 164 (25.6%) novel recurring headache occurred, heterogeneous in quality, localisation and intensity. Conclusion: We present an in-depth analysis of spontaneous cervical artery dissection-related head/neck pain characteristics and its long-term dynamics.